Hubungan Pengetahuan dan Sikap terhadap Praktik Kesehatan Rongga Mulut pada Ibu Hamil - Amaliah, Nurfitri; Widjaja, Jennifer (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2026)
Background: Oral health during pregnancy is a critical component of maternal and fetal well-being; however, it is often overlooked due to a lack of knowledge and attitude to maintain the wellness of oral health among expectant mothers. Objective: to assess the relationship between knowledge and attitude with oral health care practices among pregnant women in Made Community Health Centre, Surabaya. Methods: A descriptive cross-sectional study involving 300 pregnant women selected through purposive sampling. Data were collected using a validated structured questionnaire, and Spearman’s rank correlation analysis was applied to evaluate the relationships between variables. Results: The majority of participants fell within the 26–35 age bracket (50%) and were in their third trimester (53%). The statistical analysis revealed a significant positive correlation between knowledge and oral health practice (rs = 0.382; p < 0.001). Furthermore, a moderate and significant correlation was found between attitude and practice (rs = 0.445; p < 0.001). While the participants demonstrated generally adequate knowledge and positive attitudes, specific preventive practices—such as the use of dental floss and regular dental visits—remained suboptimal. The findings confirm that both knowledge and attitude are significant determinants of oral health behaviours, with attitude showing a slightly stronger association with practice. Conclusion: To bridge the gap between knowing and doing, continuous oral health education integrated into antenatal care services is essential. Strategies should focus on fostering positive attitudes to encourage consistent oral hygiene practices among expectant mothers.